2013
DOI: 10.1227/neu.0000000000000070
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Improved Outcomes Following Decompressive Surgery for Prostate Cancer Metastatic to the Spine

Abstract: Spinal surgery for prostate metastases improves neurological function and decreases analgesic requirements. Our findings support surgical intervention for carefully selected patients, and knowledge of preoperative hormone sensitivity and performance status may help with risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 38 publications
3
61
2
1
Order By: Relevance
“…3 did not find a statistically significant difference in the incidence rate of complications among spinal metastases based on primary tumor site. However, Ju et al 15 reported that younger age (p < 0.01) and instrumentation greater than 7 spinal levels (p = 0.03) were associated with increased odds of complication in patients with MESCC stemming from prostate cancer. Quraishi et al 36 compared complication rates based on timing of surgery and determined that the incidence of complications was similar among those treated with surgery within 24 hours (40% complication rate), between 24 and 48 hours (43%), and over 48 hours (42%) following acute presentation of neurological symptoms (p = 1.0).…”
Section: Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 did not find a statistically significant difference in the incidence rate of complications among spinal metastases based on primary tumor site. However, Ju et al 15 reported that younger age (p < 0.01) and instrumentation greater than 7 spinal levels (p = 0.03) were associated with increased odds of complication in patients with MESCC stemming from prostate cancer. Quraishi et al 36 compared complication rates based on timing of surgery and determined that the incidence of complications was similar among those treated with surgery within 24 hours (40% complication rate), between 24 and 48 hours (43%), and over 48 hours (42%) following acute presentation of neurological symptoms (p = 1.0).…”
Section: Complicationsmentioning
confidence: 99%
“…2,3,5,7,15,18,19,21,25,28,[30][31][32]34,35,37,38,40,43 Of these, 16 studies were retrospective; 1 was a longitudinal observational study; 1 was a randomized, multiinstitutional, nonblinded trial; and 1 was a semiprospective study that included both retrospectively and prospectively collected data. Surgical interventions included decompression with and without instrumentation and radiotherapy.…”
Section: Predictors Of Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…1,13,14,16,17,26,27,30,31,38,63,93,[95][96][97][98] However, surgical approaches to spinal tumors often necessitate extensive reconstruction of the spinal column and may require adjuvant chemotherapy or radiation; therefore, perioperative complication rates after spinal tumor surgery are higher than in other spinal operations. [34][35][36][46][47][48]50,52,65,67,68,78,80,81,[86][87][88]95,100 It is especially important to understand the incidence and predictive factors for adverse events in spinal oncology patients, as a single complication may be associated with morbidity, mortality, and costs. 1,31,37,46,47,52,62,70,72,79,86,95 Risk stratification of patients preoperatively is important to optimize outcomes, …”
mentioning
confidence: 99%
“…Algumas variáveis como idade, carga tumoral, expectativa de vida e capacidade funcional influenciarão na escolha das opções terapêuticas (SCIUBBA; GOKASLAN, 2006;JU et al, 2013).…”
Section: Diagnóstico E Tratamentounclassified